PENGELOLAAN SARANA DAN PRASARANA PENDIDIKAN DALAM MENUNJANG MUTU PENDIDIKAN DI SMP NEGERI 1 BUAY PEMUKA BANGSA RAJA - Cindy Fadzilla; Achadi Budi Santosa; Dian Hidayati (Jurnal Manajemen Pendidikan, 2026)
Facilities and infrastructure are essential components that support the learning process to run effectively and efficiently. The implementation of transparent, accountable, and appropriate facilities and infrastructure management will certainly provide added value to school development and improve the quality of education to be achieved. Management in public schools is carried out directly by the person in charge of facilities and infrastructure, who is a teacher at the school, along with the principal, school committee, and all teaching staff. This study aims to understand how the planning management of educational facilities and infrastructure is implemented in schools in an effort to support the quality of education. The aspects of facilities and infrastructure management discussed in this study include: (1) planning, (2) utilization, (3) inventory, (4) maintenance, and (5) disposal. This research employs a descriptive qualitative method, with data collection techniques including observation, interviews, and document analysis. The subjects of this study are the vice principal in charge of facilities and infrastructure. The results of the study indicate that the implementation of well-planned and systematic facilities and infrastructure management can improve the quality of education. Although the school is located far from urban centers, its facilities and infrastructure are not significantly inferior to those of schools located in more central areas.